Investigation of the Soils of North Bihar and Their Role in Irrigation Project - Baksi, R D; Dewan, R L (Journal of Soil and Water Conservation, 2022)
The purpose of agri-irrigation soil sur- vey is to have a knowledge of the soil resources of an area and to determine its qualities in order to put this knowledge to practical utility. Soil maps based on soil survey, indicating the location of different kinds of soil, are of great significance to the cultivators using land for the growth of crops, particularly when irrigation facilities are. made available to them. It was with these objects in view that about 32 lac acres of land in North Bihar comprising districts of Saran, Champaran, Muzaffarpur and Dar- bhanga were scientifically surveyed. The resuits of laboratory and field investigations presented in this paper indicate the salient features of the area proposed to be com- mancled by the Gandak Irrigation & Power Project in North Bihar.